Study Salmonella typhi in Cholelithiasis Patients in Related to Antibiotic Resistant and IL-37 - Raad, Alaa Zanzal; Mustafa, Amer Hameed (Iraqi Journal of Science, 2026)
Gallstones, also known as cholelithiasis, pose a significant threat to public health worldwide. While some people have recovered from typhoid fever, chronic infection with Salmonella typhi bacteria can lead to serious complications, including the development of gallstones and gallbladder cancer. This research investigated the epidemiology of S. typhi-infected gallstones related to interlukin-37. A cross-sectional study was conducted involving 125 cases of individuals aged 15 - 80 years, who visited the Erbil and Rizgari Teaching Hospitals and had their gallbladder removed. Gallbladder specimens and blood samples were collected to measure IL-37 using an ELISA assay. Additionally, an antibiogram test was performed. The study found that 101 patients (80.8%) cases had bacterial-infected cholelithiasis, while patients 24 (19.2%) did not show infection. Among these, 93 (74.4%) cases had other bacteria, while 8 (6.4%) cases had S. typhi in the gallbladder divided into gallstones 5 (4%), bile 1 (0.8%), and gallbladder tissue 2 (1.6%) cases. S. typhi forms biofilm on cholesterol gallstones more than pigment and mixed stones. The most infected age group 36–45 years were 32.8% cases, mostly females from urban areas. In 125 patients, the mean IL-37 level was 104.12 pg/ml compared with the control was 63.64 pg/ml. S. typhi was sensitive to piperacillin/tazobactam, ertapenem, meropenem, and fosfomycin, while resistant to another traditional antibiotic. In conclusion, S. typhi is more frequently found in gallstones than in the bile or gallbladder tissue in cholelithiasis patients, specifically in cholesterol-type gallstones. Most affected patients were females aged 36–45 years from urban areas. While S. typhi resistant to traditional antibiotics, it remains sensitive to ertapenem, imipenem, meropenem, and piperacillin/tazobactam. Elevated levels of IL-37 can reflect the presence of gallstones and indicate infected gallstones with S. typhi.